Optimizing Plasma Cutting Parameters for Thin Mild Steel Sheets of Various Thicknesses - Andiboyina Sireesha; D. Rupesh; K. Niranjan Kumar; K. Abhiram (International Journal of Electro-Mechanics and Material Behaviour, 2023)
Plasma machining was investigated for suitability to cut thin sheets and the quality obtained was assessed. The main objective of this investigation is to machine or cut required Mild steel sheet thicknesses and to determine the surface roughness and MRR values. Traditional cutting techniques have been discovered to be costly in terms of both time and resources. This study may be valuable to car converters, such as firms that make wheelchair-accessible automobiles or other analogous companies where the use of traditional cutting technologies is still common. In turn, a robotic plasma cutter would be a practical solution. In this experiment, mild steel with a thickness range of 3 mm to 5 mm and materials of different compositions had been cut using a plasma cutter with a controlled torch height correction. Tests were carried out by varying the plasma parameters like cutting speed, pressure, and intensity.
Keywords: Cutting Speed; MRR; Material; Plasma cutting Machine; mild steel